2015
DOI: 10.1111/bcpt.12495
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Weighting of Drug–Drug Interactions in Hospitalized Elderly

Abstract: Adverse drug reactions impact on patient health, effectiveness of pharmacological therapy and increased health care costs. This investigation intended to detect the most critical drug-drug interactions in hospitalized elderly patients, weighting clinical risk. We conducted a cross-sectional study between January and April 2014; all patients 70 years or older, hospitalized for >24 hr and prescribed at least one medication were included in the study. Drug-drug interactions were estimated by combining Stockley's,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 25 publications
0
16
1
Order By: Relevance
“…[1,3,5,23,24] In this study, most of the interactions were significant in nature, followed by minor interactions and serious interactions. Contraindicated interaction was found in only 0.1% of the case; this proportion was lower compared with a proportion of as reported in a study conducted by Juárez-Cedillo et al [25] The significant type of interactions was found prominently in patients with cardiovascular co-morbidities; whereas, minor type of interactions was observed more in diabetic patients. No significant difference was found in pharmacokinetic (21.4%) and pharmacodynamic (20.1%) interactions.…”
Section: Discussioncontrasting
confidence: 62%
“…[1,3,5,23,24] In this study, most of the interactions were significant in nature, followed by minor interactions and serious interactions. Contraindicated interaction was found in only 0.1% of the case; this proportion was lower compared with a proportion of as reported in a study conducted by Juárez-Cedillo et al [25] The significant type of interactions was found prominently in patients with cardiovascular co-morbidities; whereas, minor type of interactions was observed more in diabetic patients. No significant difference was found in pharmacokinetic (21.4%) and pharmacodynamic (20.1%) interactions.…”
Section: Discussioncontrasting
confidence: 62%
“…Regarding the severity of the DDIs, the frequency of serious and contraindicated interactions was higher than that reported in previous studies on hospitalized elderly patients (Gotardelo et al, 2014;Juárez-Cedillo et al, 2016;Pasina et al, 2013). Considering that numerous patients are often frail due to multiple diseases and complex treatment regimens, the clinical effect of these interactions should be analysed.…”
Section: Discussionmentioning
confidence: 81%
“…Fifteen studies analysed DDIs through the Drug-Reax System (also known as Micromedex),27–30 32–36 38 39 43 47 50 58 five studies analysed DDIs using Beers criteria,37 40 41 44 45 four studies analysed DDIs using the Medscape Drug Interaction Checker38 46–48 and two studies used the Epocrates Interaction Check 47 54. Ten studies evaluated DDIs with more than one type of software 15 29 35 36 38 39 42 45 47 51. Textbooks were employed in nine studies 15 29 35 38 39 42 49 51 59.…”
Section: Resultsmentioning
confidence: 99%
“…Sample size varied from 44 to 1510, totalling 9577 patients. The majority of papers were cross sectional and from developing countries: 9 studies were from Brazil,27–35 6 studies were from India,36–41 2 from Mexico,42 43 2 from Croatia,44 45 1 from Venezuela,46 1 from Serbia,47 1 from Nepal,48 1 from Iran49 and one from Ethiopia 50. The remaining 10 studies were from Spain,51 52 Norway,53 Portugal,54 Germany,55 Italy,56 Austria,57 Israel,58 Canada15 and Australia 59.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation